THE EFFECT OF THINK TALK WRITE LEARNING MODEL ASSISTED BY AUDIOVISUAL ON THE NEGOTIATION TEXT WRITING SKILLS OF GRADE X STUDENTS - Hutagalung, Nadia; Simanjuntak, Harlen; Monalisa Frince (Dharmas Education Journal (DE_Journal), 2022)
This study aims to determine the effect of the think talk write (TTW) learning model assisted by audiovisual media on the negotiation text writing skills of Grade X students at SMA Negeri 8 Medan. The research employs a quantitative experimental method with a two-group posttest-only design. The population of this study consists of all Grade X students at SMA Negeri 8 Medan, totaling 384 students. The study uses two classes as the control and experimental groups. Data analysis techniques include normality test, homogeneity test, and hypothesis testing. The control group was taught without using the Think Talk Write model assisted by audiovisual media, while the experimental group was taught using this model. The results showed that the control class had an average score of 65.93 with a standard deviation of 17.50, while the experimental class had an average score of 77.21 with a standard deviation of 15.98. The prerequisite tests indicated that the data from both the control and experimental groups were normally distributed and homogeneous. The hypothesis testing was conducted using a 5% significance level with degrees of freedom (df) = (N1 + N2) - 2 = 64. Based on the t-distribution table, the critical value at 5% significance is t_table = 1.669. Since t_calculated > t_table (2.75 > 1.669), it can be concluded that the null hypothesis (H₀) is rejected and the alternative hypothesis (H₁) is accepted.